Bending strength of steel fibre reinforced concrete ribbed slab panel / Amir Syafiq Samsudin … [et al.]. - Samsudin, Amir Syafiq; Mohd Hashim, Mohd Hisbany; Hamzah, Siti Hawa; Abu Bakar, Afidah (Institute of Research Management and Innovation and UiTM Press, 2018)
Nowadays, demands in the application of fibre in concrete increase gradually as an engineering material. Rapid cost increment of material causes the increase in demand of new technology that provides safe, efficient and economical design for the present and future application. The introduction ofribbed slab reduces concrete materials and thusthe cost, but the strength of the structure also reduces due to the reducing of material. Steel fibre reinforced concrete (SFRC) has the ability to maintain a part of its tensile strength prior to crack in order to resist more loading compared to conventional concrete. Meanwhile, the ribbed slab can help in material reduction. This research investigated on the bending strength of 2-ribbed and 3-ribbed concrete slab with steel fibre reinforcement under static loading with a span of 1500 mm and 1000 mm x 75 mm in cross section. An amount of 40 kg/m steel fibre of all total concrete volume was used as reinforcement instead of conventional bars with concrete grade 30 N/mm2 . The slab wastested underthree-point bending. Load versus deflection curve was plotted to illustrate the result and to compare the deflection between control and ribbed slab. Thisresearch showsthat SFRCRibbed Slab capable to withstand the same amount of load as normal slab structure, although the concrete volume reduces up to 20%.